RISK OF INJURY DEVELOPMENT DUE TO SURGICAL POSITIONING: AN OBSERVATIONAL STUDY (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objective: To classify the risk of developing injury due to surgical positioning. Method: Observational, longitudinal, prospective study with a quantitative approach carried out in a public hospital, with 135 patients undergoing elective surgery. Instruments containing sociodemographic, clinical, and surgical characteristics and a risk assessment scale for the development of injuries due to surgical positioning were used. Descriptive analysis, Fisher’s exact test or χ2 test and odds ratio association measure were used as appropriate. Results: Most participants were male (51.11%), adults (52.59%) and were classified as having a higher risk for developing injuries due to surgical positioning (51.85%). Elderly, hypertension, diabetes mellitus and urological surgeries were statistically significant (p < 0.05) for a higher risk of developing lesions. The incidence of pressure injuries was 0.74%, with observation only in the sacral region. Conclusion: There was a greater risk of developing lesions due to surgical positioning and low incidence of pressure injury. Perioperative nursing should incorporate validated risk measurement tools into care practice for safe, individualized and quality care for surgical patients.